Retrospective analysis of endemic melasma patients - Serkan Demirkan; Özgür Gündüz; Cemile Dayangan Sayan (PAGEPress Publications, 2017)
Melasma is an acquired diffuse hypermelanosis characterized by localized, symmetrical, irregular, light-to-dark brown maculae occurring in sun-exposed areas of skin. The aim of this retrospective study was to determine demographics of patients, analysis of etiologic factors, clinical features, efficacy and side effects of available topical treatments due to high incidence of melasma patients. In this study melasma patients in Birecik State Hospital were investigated retrospectively. Between January 2014 and October 2015, 1008 patients had diagnosis of melasma in 49,809 applications of 24,603 different patients who admitted to Dermatology Outpatient Clinics. Of the 1008 patients, 263 had completed 3-month treatment period. These patients did not receive treatment in June, July, August and September. All melasma patients were rural and dealing with agriculture. There was no significant difference between female and male patients in terms of age. Of the 253 female melasma patients, only 2 of them had not child and none of them were using hormone drug. Of the 263 patients with melasma, Fitzpatrick skin type was 3 in 79 (30%) patients, 4 in 184 (70%) patients. Şanlıurfa city showed higher fertility rate, sun exposure, and skin type than Turkey as a whole. These predisposing factors may explain higher melasma occurrence in Şanlıurfa. Patient information about preventive measures and treatment play important role in treatment of cosmetic condition. The most important measure seems to advise patients about sun-protection especially during pregnancy.